Conversion From Sirolimus to Everolimus in Long‐Term Liver Graft Recipients. (30th January 2017) - Weiler, Nina; Bilge, Nigar; Troetschler, Sven; Vermehren, Johannes; Schnitzbauer, Andreas Anton; Herrmann, Eva; Sarrazin, Christoph; Zeuzem, Stefan; Welker, Martin‐Walter
Abstract: Immunosuppression by inhibition of the mechanistic target of rapamycin (mTOR) is a promising approach after liver transplantation. The mTOR inhibitor sirolimus was used in selected liver graft recipients despite safety concerns and lack of approval. Everolimus is another mTOR inhibitor approved after liver transplantation. It is currently unknown, whether conversion of sirolimus to everolimus is safe in long‐term liver graft recipients. Long‐term liver graft recipients treated with sirolimus were converted to everolimus. A systematical analysis of biochemical and clinical data before and after conversion was performed. Sixteen patients were included (female/male, 8/8). Median (range) age at conversion was 66 years (49–78 years), and patients were converted at a median (range) of 10.1 years (4.0–22.3 years) after liver transplantation. In the majority of patients, no dose adjustment was needed after conversion. No rejection and no cytomegalovirus replication episodes were observed. Furthermore, no differences were found with respect to kidney function, diabetes mellitus, or blood pressure before and after conversion. Bilirubin serum concentration was lower, whereas aspartate aminotransaminase, alanine aminotransferase, and triglycerides serum concentrations were higher after conversion to everolimus. Neither clinical‐ nor graft‐associated significant complications were observed after conversion from sirolimus to everolimus in long‐term liver graft recipients. Everolimus‐based immunosuppression may be offered to patients after liver transplantation formerly treated with sirolimus.